Mice with altered serotonin 2C receptor RNA editing display characteristics of Prader–Willi syndrome - Michael V. Morabito; Atheir I. Abbas; Jennifer L. Hood; Robert A. Kesterson; Michelle M. Jacobs; David S. Kump; David L. Hachey; Bryan L. Roth; Ronald B. Emeson (Neurobiology of Disease, 2010)
RNA transcripts encoding the 2C-subtype of serotonin (5HT2C) receptor undergo up to five adenosine-to-inosine editing events to encode twenty-four protein isoforms. To examine the effects of altered 5HT2C editing in vivo, we generated mutant mice solely expressing the fully-edited (VGV) isoform of the receptor. Mutant animals present phenotypic characteristics of Prader–Willi syndrome (PWS) including a failure to thrive, decreased somatic growth, neonatal muscular hypotonia, and reduced food consumption followed by post-weaning hyperphagia. Though previous studies have identified alterations in both 5HT2C receptor expression and 5HT2C-mediated behaviors in both PWS patients and mouse models of this disorder, to our knowledge the 5HT2C gene is the first locus outside the PWS imprinted region in which mutations can phenocopy numerous aspects of this syndrome. These results not only strengthen the link between the molecular etiology of PWS and altered 5HT2C expression, but also demonstrate the importance of normal patterns of 5HT2C RNA editing in vivo.